Foreign direct investment end exchange rate volatility: evidence from four East Asian country / Muhammad Nurulhakim Abd Rahim - Abd Rahim, Muhammad Nurulhakim (Faculty of Business Management, 2017)
This paper examines the relationship between Foreign Direct Investment (FDI) and selected macroeconomic determinants such as Exchange Rate Volatility, Inflation Rate and Trade Openness. It is found that exchange rate volatility and trade openness have significant relationships towards FDI meanwhile inflation rate shows insignificant relationship towards FDI. Secondary data was collected from World Development Indicator (WDI) website from year 2006 to 2014 which contain annually data from four East Asian countries namely Malaysia, China, Thailand and the Philippines. The sample data comprises of total 36 observations in this paper. The researcher used the well-known software Eviews8 in order to run the model and estimate the regression. Besides, this paper also employed the Breusch- Godfrey Serial Correlation LM test, Autoregressive Conditional Hetroscedasticity (ARCH) test, Jarque- Bera test, Normality test and more thus encountered that there is no serious multicollinearity problem, no autocorrelation, no heteroscedasticity, and error term is normally distributed hence model is correctly specified. These practical results help potential investors to correlate the relationships of selected macroeconomic variables proxy to FDI and assisting in their decision making.